2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5333506
|View full text |Cite
|
Sign up to set email alerts
|

The strathclyde brain computer interface

Abstract: Brain-computer interfaces (BCI) offer potential for individuals with a variety of motor and sensory disabilities to control their environment, communicate, and control mobility aids. However, the key to BCI usability rests in being able to extract relevant time varying signals that can be classified into usable commands in real time. This paper reports the first success of the Strathclyde BCI controlling a wheelchair on-line in Virtual Reality. Surface EEG recorded during wrist movement in two different direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…This suggests that strategies in the interface which support the user or attempt to detect inadvertent command sequences should be adopted. The accuracy levels reported in recent publications tend to [12], [17] conform to users expectations. Significantly, however, concerning the test of command operational accuracy, the users with disabilities did not achieve a level of operation which conformed to their specified expectations.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…This suggests that strategies in the interface which support the user or attempt to detect inadvertent command sequences should be adopted. The accuracy levels reported in recent publications tend to [12], [17] conform to users expectations. Significantly, however, concerning the test of command operational accuracy, the users with disabilities did not achieve a level of operation which conformed to their specified expectations.…”
Section: Discussionsupporting
confidence: 65%
“…It can be argued that for the user the single overriding performance measure is of command classification accuracy within a reasonable timescale [11]. This is particularly significant when placed within the context of BCI where commonly applications are not wholly accurate: 70% [8], 68-77% [12] 97.5% [17] and the operation of an interface may require a trade-off between technological factors and usage patterns. In attempting to answer what constitutes a reliable measure we have provided a test application which focuses upon the user's perception of reliability.…”
Section: Contrasting Levels Of Accuracy In Command Interaction Sequenmentioning
confidence: 99%
See 1 more Smart Citation
“…First, these studies concerned mainly the evaluation phase, i.e., the evaluation of prototypes and of the appropriateness of applications (e.g., (Nijboer et al, 2010)), to the detriment of the early design phase aiming to understand the context of use or to specify the user needs (e.g., (Blain-Moraes et al, 2012)). Second, the majority of studies used only one method: the user based test is mainly used to evaluate the usability (e.g., (Valsan et al, 2009)) and the usefulness (e.g., (Yan et al, 2008)) ; the focus group to characterise the acceptability (e.g., (BlainMoraes et al, 2012)) and the questionnaire is used to measure the user experience (e.g., (Van de Laar et al, 2011)) and, in longitudinal studies, to assess the application's appropriateness (e.g., (Nijboer et al, 2010)). Third, the assessments of BCI videogames focused on a single criterion which was mainly the usability (e.g., Holz et al, 2013;Gürkök et al, 2014) at the expense of other criteria such as immersion, presence (e.g., (Hakvoort et al, 2011)) or usefulness (e.g., (Yan et al, 2008)).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that BCI technology can be applied to many assistive technologies: -wheelchair control [4], [5], [6] computer speller [7], [8], [4], webbrowser [9], environment control [10], [11], [12] and computer games [13], [14]. Smart homes technology is also an active area of research [15], [16], both for assistive applications and to enhance 'lifestyle'.…”
Section: Introductionmentioning
confidence: 99%